Hubungan Status Gizi dan Genetik Ibu dengan Usia Menarche pada Remaja Putri - Nel Efni; Tina Yuli Fatmawati (Prosiding Seminar Kesehatan Nasional, 2022)
Menarche is an important event in the life of a young woman. The results of the study showed an increase in awareness of the impact of menstrual management practices on health, education, and psychosocial for women and girls in low- and middle-income countries. Â This study aims to determine the relationship between nutritional status and maternal genetics with the age of menarche in female students at SMP Nurul Falah Jambi City.Design This study is a quantitative study with the Cross Sectional method (cross-sectional) which aims to see the relationship between the dependent variable (dependent) and the independent variable (independent). This research was conducted at SMP Nurul Falah in Jambi City from December to February 2021 with a total population sample of 89 students. Data were analyzed by univariate analysis and bivariate analysis. The results showed that there was from 89 respondents who had poor nutritional status, namely 67 respondents (76%), respondents who had maternal genetics with fast/late menarche were 45 respondents (51%), there was a relationship between nutritional status and maternal genetics with the age of menarche with the P value is 0.012 and 0.025